2009
DOI: 10.1021/ct900352f
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of the Benzyl Radical: Mechanism, Thermochemistry, and Kinetics for the Reactions of Benzyl Hydroperoxide

Abstract: Oxidation of the benzyl radical plays a key role in the autoignition, combustion, and atmospheric degradation of toluene and other alkylated aromatic hydrocarbons. Under relevant autoignition conditions of moderate temperature and high pressure, and in the atmosphere, benzyl reacts with O2 to form the benzylperoxy radical, and the further oxidation reactions of this radical are not yet fully characterized. In this contribution, we further develop the reaction chemistry, thermodynamics, and kinetics of benzyl r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 28 publications
4
62
0
Order By: Relevance
“…hDE d i estimates have ranged from 2000 cm À1 for the benzyl radical, 52,53 1000 cm À1 for a C 7 heterocyclic ring, 55 718 cm À1 for a C 10 H 10 biheterocycle, 54 500 cm À1 for pyrazole, 56 fulveneallene 57 and benzyl hydroperoxide, 58 and 260 cm À1 for 2,5-dimethylfuran 29-31 and furan. Many recent literature studies have assumed constant hDE d i values for similar systems (large aromatic molecules).…”
Section: Methodsmentioning
confidence: 99%
“…hDE d i estimates have ranged from 2000 cm À1 for the benzyl radical, 52,53 1000 cm À1 for a C 7 heterocyclic ring, 55 718 cm À1 for a C 10 H 10 biheterocycle, 54 500 cm À1 for pyrazole, 56 fulveneallene 57 and benzyl hydroperoxide, 58 and 260 cm À1 for 2,5-dimethylfuran 29-31 and furan. Many recent literature studies have assumed constant hDE d i values for similar systems (large aromatic molecules).…”
Section: Methodsmentioning
confidence: 99%
“…In daytime, the reaction of aromatic hydrocarbons with hydroxyl radicals is the major atmospheric loss process [14][15][16]. Several previous experimental [17][18][19] and theoretical [20][21][22][23][24][25][26] studies have unraveled the elementary reactions involved in aromatic oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that in the presence of OH radical the main reaction path is OH addition to the aromatic ring to form a xylene-OH adduct (consuming $90% of OH radicals) with Habstraction from one methyl group to form a methylbenzyl radical (consuming $10% of OH radicals) being the minor route [18,[31][32][33][34]. In addition, theoretical investigations have mainly focused on OH-addition to xylene and the fate of xylene-OH adducts and intermediates [15,26,31,[34][35][36], whereas the H-abstraction mechanism for p-xylene oxidation following the initial OH attack and subsequent products have only been studied experimentally [22,25,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…For salicylic alcohol, an approximate determination using the group additivity Joback-Reid method [40] is present in the literature [41], giving a value of -67.12 kcal/mol in good agreement with our recommended value. Da Silva and Bozzelli [42,43], using a simpler theoretical method (G3B3) suggested a value of 31.1 kcal/mol for the benzyloxy radical and 29.6 kcal/mol for the benzylperoxy radical. Both values are larger than the best ones we found and, moreover, they suggest that the latter is more stable than the former, contrary to what we found.…”
Section: Resultsmentioning
confidence: 99%